Systemic Inflammation and Cerebral Palsy Risk in Extremely Preterm Infants. (December 2014) - Kuban, Karl C. K.; O'Shea, T. Michael; Allred, Elizabeth N.; Paneth, Nigel; Hirtz, Deborah; Fichorova, Raina N.; Leviton, Alan
The authors hypothesized that among extremely preterm infants, elevated concentrations of inflammation-related proteins in neonatal blood are associated with cerebral palsy at 24 months. In 939 infants born before 28 weeks gestation, the authors measured blood concentrations of 25 proteins on postnatal days 1, 7, and 14 and evaluated associations between elevated protein concentrations and cerebral palsy diagnosis. Protein elevations within 3 days of birth were not associated with cerebral palsy. Elevations of tumor necrosis factor-α, tumor necrosis factor-α-receptor-1, interleukin-8, and intercellular adhesion molecule-1 on at least 2 days were associated with diparesis. Recurrent-persistent elevations of interleukin-6, E-selectin, or insulin-like growth factor binding protein-1 were associated with hemiparesis. Diparesis and hemiparesis were more likely among infants who had at least 4 of 9 protein elevations that previously have been associated with cognitive impairment and microcephaly. Repeated elevations of inflammation-related proteins during the first 2 postnatal weeks are associated with increased risk of cerebral palsy.